Integrative genomic analysis in African American children with asthma finds three novel loci associated with lung function. Issue 2 (29th September 2020) - Goddard, Pagé C.; Keys, Kevin L.; Mak, Angel C. Y.; Lee, Eunice Y.; Liu, Amy K.; Samedy‐Bates, Lesly‐Anne; Risse‐Adams, Oona; Contreras, María G.; Elhawary, Jennifer R.; Hu, Donglei; Huntsman, Scott; Oh, Sam S.; et al.
Abstract: Bronchodilator (BD) drugs are commonly prescribed for treatment and management of obstructive lung function present with diseases such as asthma. Administration of BD medication can partially or fully restore lung function as measured by pulmonary function tests. The genetics of baseline lung function measures taken before BD medication have been extensively studied, and the genetics of the BD response itself have received some attention. However, few studies have focused on the genetics of post‐BD lung function. To address this gap, we analyzed lung function phenotypes in 1103 subjects from the Study of African Americans, Asthma, Genes, and Environment, a pediatric asthma case–control cohort, using an integrative genomic analysis approach that combined genotype, locus‐specific genetic ancestry, and functional annotation information. We integrated genome‐wide association study (GWAS) results with an admixture mapping scan of three pulmonary function tests (forced expiratory volume in 1 s [FEV1 ], forced vital capacity [FVC], and FEV1 /FVC) taken before and after albuterol BD administration on the same subjects, yielding six traits. We identified 18 GWAS loci, and five additional loci from admixture mapping, spanning several known and novel lung function candidate genes. Most loci identified via admixture mapping exhibited wide variation in minor allele frequency across genotyped global populations. Functional fine‐mapping revealed an enrichment of epigenetic annotations from peripheral blood mononuclear cells, fetal lung tissue, and lung fibroblasts. Our results point to three novel potential genetic drivers of pre‐ and post‐BD lung function: ADAMTS1, RAD54B, and EGLN3 .